, ; Ownership structures, profitability and debts of agricultural large firms in the Volgograd region - Eberhard Schulze; Peter Tillack; Sergej Gerasin (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2001)
34 100 - . 2000 . - - 18. 31 , , , , , , , , . . - 2,6 48,5 . 53,0 % 53,3 % . 14 23 . -- . ( 20 000 ), ( 4 000 ). - , . 1999 . , , 3,4 %. - , - , , 25,5 %. 59 - 15 , 9 35 . – – Discussion Paper 34 contains information on property relations and profitability of 100 Russian large-scale farm enterprises, gathered in interviews in the Volgograd region in 2000. They are an integrated part of research activities concerning the privatisation and restructuring of farm enterprises in Central and Eastern Europe and take up the subject of Discussion Paper 18. 31 questions were formulated. The answers were evaluated using multivariate statistical methods. Comprehensive knowledge was obtained about number and size of land and capital shares, voting mode, indebtedness, cost of social security contributions for the employees and of the support for household plots and ensuing consequences for the profitability of enterprises. Within a farm, land shares are principally of the same size varying between 2.6 and 48.5 hectares. Farm workers hold 53.0 % of the land shares and 53.3 % of the capital. In 14 out of 23 corporations the voting mode was not in agreement with the legal rules. A significant nonlinear relationship between acreage and profitability could be confirmed. Compared with medium-sized farms, the profitability was higher in some very large (>20 thousand ha) and also in relatively small farms (approx. 4 thousand ha). In case of the latter it was to be checked up whether and which way restructuring would be feasible in order to raise the profitability level. The average cost efficiency of large-scale farms as used in Russia for reporting on profitability was 3.4 % in 1999. If the costs of social security contributions by the farms for the workers, support for family farms and sometimes unusually high depreciation rates are neglected, the average cost efficiency is clearly higher (25.5 %). 15 farms out of 59 believe that they are able to settle the debt problem under their own steam; 9 hope for contributions by the government, and 35 expecta full assumption of their debts by the state.
urn:nbn:de:gbv:3:2-22991
Keywords: O13; O47; 330; Large-scale Farms; Land Ownership; vote mode; profitability; debts; Landwirtschaft; Großunternehmen; Eigentümerstruktur; Corporate Governance; Rentabilität; Verbindlichkeiten; Schätzung; Wolgograd (Oblast); Russland